2016
DOI: 10.1242/jcs.198002
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-severing activity of AAA+ ATPase Katanin is essential for female meiotic spindle assembly

Abstract: In most animals, female meiotic spindles are assembled in the absence of centrosomes. How microtubules (MTs) are organized into acentrosomal meiotic spindles is poorly understood. In Caenorhabditis elegans, assembly of female meiotic spindles requires MEI-1 and MEI-2, which constitute the microtubule-severing AAA+ ATPase Katanin. However, the role of MEI-2 is not known and whether MT severing is required for meiotic spindle assembly is unclear. Here, we show that the essential role of MEI-2 is to confer MT bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, our data suggest that the initial steps of the transition from metaphase to anaphase are due to changes in microtubule turnover rate and growth and not mediated by katanin dependent severing. This is surprising since earlier work clearly demonstrated the importance of severing during spindle assembly (Srayko et al 2006, McNally et al 2011, McNally et al 2014, Connolly et al 2014, Joly et al 2016). Estimates of the number of Katanin-mediated cutting events by counting lateral defects in partial EM reconstructions of meiotic spindles at earlier stages had found a large number of cutting events in wildtype spindles (Srayko et al 2006).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, our data suggest that the initial steps of the transition from metaphase to anaphase are due to changes in microtubule turnover rate and growth and not mediated by katanin dependent severing. This is surprising since earlier work clearly demonstrated the importance of severing during spindle assembly (Srayko et al 2006, McNally et al 2011, McNally et al 2014, Connolly et al 2014, Joly et al 2016). Estimates of the number of Katanin-mediated cutting events by counting lateral defects in partial EM reconstructions of meiotic spindles at earlier stages had found a large number of cutting events in wildtype spindles (Srayko et al 2006).…”
Section: Resultsmentioning
confidence: 82%
“…Along with this microtubule reorganization, chromosomes are segregated to extrude half of the genetic material as polar bodies. The underlying mechanism of the microtubule reorganization is not very well understood, and several mechanisms could be involved, for instance katanin-mediated severing as reported for C. elegans meiosis I (Joly et al 2016, Srayko et al 2006), transport of microtubules as reported for C. elegans and Xenopus meiotic spindles (Mullen & Wignall 2017, Brugués et al 2012) or changes in microtubule polymerization dynamics a shown for Xenopus meiotic spindles (Brugués et al 2012, Needleman et al 2010). Here we have generated complete 3D reconstructions of meiotic spindles in C. elegans at different stages and combined this ultrastructural analysis with light microscopy and simulations to investigate the rearrangement of microtubules during meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spindle reformation defects, cell division alterations, and mislocalization of cytokinesis regulators at the midbody in SRCAP-depleted cells, together with specific interactions detected in telophase-synchronized cells provides evidence that SRCAP participates in two different steps of cell division; it may ensure proper chromosome segregation, regulating microtubule organization and mitotic spindle assembly, and it may be required for midbody function during abscission, participating in the recruitment of cytokinesis regulators, such as MKLP2, Aurora B, PLK1, Cep55, Anillin, Alix, and Spastin (and possibly other factors) to the midbody, ensuring the final cut that is essential for proper abscission. In this context, crosstalk between SRCAP and cytokinesis regulators may occur to control midbody architecture and function similar to the examples in the literature(38).Several ATPases, such as Katanin, Cdc48/p97, ISWI, VPS4, and Spastin, interact with microtubules and play direct roles in mitosis and cytokinesis(57)(58)(59). The ESCRT-III complex protein CHMP1B recruits Spastin to the midbody(58).…”
mentioning
confidence: 75%